Board Gender, Foreign Expatriate and Accounting Conservatism In Agricultural Institutions - Simon O. ILOGHO; Uwalomwa UWUIGBE; Olayinka AKINLO; Olubukola R. UWUIGBE; Ijachi O. IJACHI; Busola E. KEHINDE (Communications of International Proceedings, 2021)
Diversity in management affects business policies such as dividend policy and other financial, R&D or investment decisions. Prior studies have observed that certain workforce demography has a more prudence tendency and recognise bad new earlier than other counterparts. The study investigated the national diversity and the gender diversity aspect of diversity. The study examined the effect of these two sets of diversity on conservatism practices. This study examined the five listed agricultural institutions in Nigeria from six years (2014 to 2019). The ordinary least square regression method was adopted to analyse the data extracted from the annual reports sampled firm. Data were extracted from these institutions' annual reports from authentic websites such as the Nigerian stock exchange websites and the African financial website. The findings from the result reveal that gender diversity does not have a significant influence over conservative practices. The findings also reveal that national diversity influences conservative practices. The study recommends maintaining statutory board size and the inclusion of a foreign board member to improve decision-making, corporate governance, and financial reporting quality.
Keywords: Market value; Board diversity; Corporate Governance; Accounting conservatism